A multicenter retrospective controlled study of the Pipeline™ and Tubridge™ Flow Diverter devices for intracranial wide-necked aneurysms - Cai, Heng; Yang, Fangyu; Xu, Yousong; Geng, Yu; Li, Jinwei; Li, Yugang; Fu, Kailei; Liu, Chang; Wang, Meiyan; Li, Zhiqing (Frontiers in Neurology, 2022)
Purpose To compare the safety and efficacy of PipelineTM and TubridgeTM Flow Diverter devices (FDs) in the treatment of intracranial wide-necked aneurysms. Methods We retrospectively analyzed the clinical data of 92 patients with intracranial wide-necked aneurysms who were treated with those two flow-diverter devices (FDs) at four participating centers between July 2012 and December 2020. Results This study included 92 patients who underwent endovascular therapy using either Pipeline™ (n = 39) or TubridgeTM (n = 53) for treating intracranial wide-necked aneurysms. The periprocedural complication developed in 2.56% (1/39) patients of Pipeline group and 3.77% (2/53) patients of the TubridgeTM group. During perioperative period, one patient in Pipeline™ group showed subarachnoid hemorrhage (2.56%, 1/39) and two ischemic complications in the Tubridge™ group (3.77%, 2/53). Follow-up assessments were conducted on 31 patients (79.49%) in the Pipeline™ group (the mean follow-up period was 9.7 ± 3.3 months). The rate of complete aneurysm occlusion at the final angiographic follow-up was 77.42%. Patients with a modified Rankin scale (mRS) score of 0.44 ± 0.31. Follow-up assessments were conducted on 42 patients (79.25%) in the TubridgeTM group (the mean follow-up period was 9.1 ± 4.4 months). The rate of complete aneurysm occlusion at the final angiographic follow-up was 85.71%. Patients with mRS score of 0.52 ± 0.28. Three patients showed parent artery stenosis, and one showed parent artery occlusion. Conclusion Both the PipelineTM and TubridgeTM are safe and effective for the treatment of intracranial wide-necked aneurysms, with no significant difference in the rate of complete aneurysm occlusion and perioperative complications between the two FDs.